Analytical determination of the stress-strain state of soil mass during tunnelling - A. Z. Ter-Martirosyan; V. V. Rud (Vestnik MGSU)
Introduction. One of the effective approaches to assessing the impact of tunnel construction works involves a comprehensive approach to problem-solving, including determination of the face-support pressure to ensure the stability of the tunnel face and assessment of additional surface movements that occur during tunnel construction. This approach is justified by the fact that actual displacements can be close to predicted ones when the optimal face-support pressure is selected and there is no face loss of soil, which could lead to unforeseen deformations. However, it should be noted that the method for calculating pressure presented in the current standard is a preliminary forecast and requires constant adjustment of the pressure during tunnel construction works.Materials and methods. In this work, the authors adapted Melan’s problem formulation with a horizontal load parallel to the surface to assess the change in the stress-strain state of the soil mass before tunnel face excavation due to the application of the face-support pressure. The problem formulation corresponds to the stage of work preparation before excavation of the soil for the installation of a precast concrete lining ring into its design position.Results. Based on the analytical equations formulated in the MathCAD software environment, isopoles of vertical and horizontal stresses, and vertical deformations were created. The obtained isopoles were compared with isopoles generated in the Plaxis 2D software using similar parameters to validate the results. Additionally, isopoles of the soil mass under the influence of the face-support pressure, considering self-weight stresses, were obtained to establish a more realistic stress-strain state of the mass in which a tunnel is being constructed.Conclusions. The analysis of the research results has shown that the isopoles are quantitatively and qualitatively similar to each other. The method proposed by the authors can be adapted with appropriate modifications to adjust the face-support pressure during construction, which is necessary both to ensure the stability of the tunnel face during construction and to minimize the impact of the face-support pressure on the ground surface.